Eddy‐induced carbon transport across the Antarctic Circumpolar Current. Issue 9 (7th September 2017) - Moreau, Sébastien; Penna, Alice Della; Llort, Joan; Patel, Ramkrushnbhai; Langlais, Clothilde; Boyd, Philip W.; Matear, Richard J.; Phillips, Helen E.; Trull, Thomas W.; Tilbrook, Bronte; Lenton, Andrew; Strutton, Peter G.
Abstract: The implications of a mesoscale eddy for relevant properties of the Southern Ocean carbon cycle are examined with in situ observations. We explored carbon properties inside a large ( 190 km diameter) cyclonic eddy that detached from the Subantarctic Front (SAF) south of Tasmania in March 2016. Based on remote sensing, the eddy was present for 2 months in the Subantarctic Zone (SAZ), an important region of oceanic carbon dioxide (CO2 ) uptake throughout the annual cycle and carbon subduction (i.e., where mode and intermediate waters form), before it was reabsorbed into the SAF. The eddy was sampled during the middle of its life, 1 month after it spawned. Comparatively, the eddy was 3°C colder, 0.5 practical salinity unit fresher, and less biologically productive than surrounding SAZ waters. The eddy was also richer in dissolved inorganic carbon (DIC) and had lower saturation states of aragonite and calcite than the surrounding SAZ waters. As a consequence, it was a strong source of CO2 to the atmosphere (with fluxes up to +25 mmol C m −2 d −1 ). Compared to the SAF waters, from which it originated, DIC concentration in the eddy was 20 μmol kg −1 lower, indicating lateral mixing, small‐scale recirculation, or eddy stirring with lower‐DIC SAZ waters by the time the eddy was observed. As they are commonly spawned from the Antarctic Circumpolar Current, and as 50% of them decay in the SAZ (the rest being reabsorbed by the SAF‐N), these types of eddies may represent a significant south‐north transport pathway for carbon across the ACC and may alter the carbon properties of SAZ waters. Key Points: We sampled a cold‐core cyclonic eddy that detached from the Subantarctic Front (SAF) and entered the Subantarctic Zone (SAZ) in March 2016 The eddy was a strong CO2 source to the atmosphere, relatively biologically unproductive, and DIC‐rich compared to surrounding SAZ waters Carbon dynamics inside the eddy indicated that lateral exchange of DIC‐rich eddy waters occurred with surrounding SAZ waters